Assessment of ear infection in children attending Dalhatu Araf specialist Hospital, Lafia - Agbawu M. Agbawu; Hassan Ikrama; Amadou Talfi Zakou; Ngolo Jebes Lamini; Celestine Osanga; Attari Nasara Dogara; Lambo Yamusa Wakili; Daniel Abah Augustine; Muhammad Maryam Hassan; Regina Aluku; Caleb Luka Kyari; Aleruchi Chuku (Elsevier, 2023)
Bacterial infection of the ear, especially amongst children from low-income countries, is a major cause of hospitalization, presenting in different forms and severity. The prevalence and antibiotic profile of bacteria associated with ear infection amongst children between the ages 0-10years presenting with symptoms was determined using standard microbiological procedures and Kirby-Bauer disk diffusion methods. The results showed an 89.6% prevalence rate of bacterial ear infections, with males and children aged 0-1 years accounting for 53.7% and 28.9% of cases respectively. Pseudomonas spp. was the most prevalent (32.6%) bacteria isolated, while Klebsiella spp. was the least prevalent (8.9%). Male children had higher distribution and presence of bacterial growths than their female counterparts. Antimicrobial assay revealed high susceptibility rates as well as multidrug resistance of the bacterial isolates to the antibiotics tested. Cefuroxime and Augmentin were most effective against all isolates. This study showed a high prevalence of bacterial-associated ear infections dominated by Pseudomonas spp. and more prevalent in males and children between 0 and 3 years old. This calls for improved postnatal care education and child hygiene by nursing mothers, midwives and nannies to forestall and prevent any public health challenge that might arise from the uncontrolled spread and increase in pathogenicity of infections caused by the isolates.